Olive tree response to applied phosphorus in field and pot experiments - Ferreira, Isabel Q. (2018)
Phosphorus (P) application in olive orchards is very common in the Mediterranean basin although experimental evidence of crop response to applied P is practically non-existent. In this work soil P and tree P nutritional status of the olive groves of NE Portugal were assessed from a population of 1808 soil and 2252 leaf samples. Plant response to applied P was evaluated from two field and two pot experiments carried out with the cultivar ‘Cobrançosa’. The analyses of soil and leaf samples of the olive orchards of the region indicate that P fertilizer recommendations should be based on leaf rather than on soil analyzes, since the latter seems to overestimate the need for P. The field and pot experiments hardly showed any positive response to P applications, which is a sign that the use of P fertilizer in olive can be substantially reduced. Nonetheless, in one pot experiment, P application significantly increased total dry matter yield during three consecutive years, in a strict association with higher tissue P concentrations and enhanced photosynthetic activity, as revealed by gas exchange and chlorophyll fluorescence traits. The experimental results also showed that the roots can uptake and store P when available in the soil, which may buffer the levels of P in the shoots. The acid phosphate activity can provide useful information but deserves caution in the interpretation of results since it depends not only on the availability of inorganic P in the soil, but also on the available organic substrate and pH.